2014
DOI: 10.1007/s12035-014-8812-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Transplanted Neural Precursors Embedded on PLA/CS Scaffold in an Animal Model of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an immune-mediated demyelinating disease of the central nervous system (CNS). Cell transplantation may be an attractive therapeutic approach for MS which may promote remyelination and suppress the inflammatory process. Neural precursor cells are promising in transplantation strategies to treat an injury to the CNS, because of their ability to differentiate into neural cells. Here, we investigated the use of polylactic acid/chitosan (PLA/CS) scaffold as 3D system which increases neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Cografting autologous nerve grafts with biomaterial polymer nerve scaffolds presupposes biocompatibility between both. Evidence for neural cell/chitosan biocompatibility comes from an animal model of multiple sclerosis developed by Hoveizi et al [123]. These authors have noted the role of polylactic acid/chitosan (PLA/CS) scaffold in increasing neural cell differentiation.…”
Section: Chitosan As An Artificial Nerve Graft Scaffold Fulfills Requmentioning
confidence: 99%
“…Cografting autologous nerve grafts with biomaterial polymer nerve scaffolds presupposes biocompatibility between both. Evidence for neural cell/chitosan biocompatibility comes from an animal model of multiple sclerosis developed by Hoveizi et al [123]. These authors have noted the role of polylactic acid/chitosan (PLA/CS) scaffold in increasing neural cell differentiation.…”
Section: Chitosan As An Artificial Nerve Graft Scaffold Fulfills Requmentioning
confidence: 99%
“…Our results showed that KI67 and Nestin in the spinal cord were significantly enhanced after BSYSC treatment 40 dpi in EAE mice, revealing the underlying potential of BSYSC on enhancing neural stem cell proliferation. Neural stem cells can be differentiated into different phenotypes, repairing injured neurons, glial cells and axons [43, 44], thus promoting functional recovery in EAE mice. Whereas no statistical difference of KI67 and Nestin was found in the brain in this experiment, this might be related to the severity of the inflammation and demyelination in spinal cord of EAE mice [45].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Haddad et al firstly decorated PLA scaffolds with polyallylamine to introduce amine groups and then functionalized them with epidermal growth factor to create a medium for supporting the proliferation of Neural Stem-Like Cells even in the absence of soluble growth factors for 14 days [99]. In another interesting example, Hoveizi et al modified PLA scaffold with chitosan to increase its biocompatibility and affinity to PC12 cells for nerve tissue engineering purposes [100]. It has been reported that the concentration of PLA and its blending with other polymers or biomaterials can affect physiochemical properties of scaffolds for nerve tissue engineering.…”
Section: Plamentioning
confidence: 99%